Program Penguatan Bisnis BUMNag Sungai Kamuyang Kenagarian Sungai Kamuyang Kabupaten Lima Puluh Kota - Dwi Yuzaria; Rusjda Khairati; Adisti Rastosari; A. Irzal Rias; Daz Edwiza (Warta Pengabdian Andalas, 2021)
BUMDes is a legal entity established by the village to manage a business, utilize assets, develop investment and productivity, provide services, and provide other types of business for the most excellent welfare of the village community. The BUMDes itself is named as BUMNag in West Sumatra. The purpose of the program was to improve the business capability of the management team in managing the BUMNag business professionally. This program was designed as a training and mentoring of adult learning method. This program has been implemented from October 11, 2021, to November 30, 2021. The results achieved from this program include 1) mapping of BUMNag business indicators, 2) business training for BUMNag management teams, 3) business mentoring and consultation for BUMNag management teams, assisting the management team in identifying potential business units, and compiling a draft business plan. The number of participants involved in this activity was up to 28 people, consisting of the head of Sungai Kamuyang village and his apparatus, the BUMNag management team, and community leaders in Sungai Kamuyang, Lima Puluh Kota regency.